שיטות אכילה סגפניות ולימוד תורה בפסקיהם של ר’ משה מאוורו ובני חוגו - קנרפוגל אפרים (מחשבת ישראל, 2021)
Scholarship has noted that the Tosafists Moses b. Shne’ur of Evreux and his brother Samuel (d. c. 1255) endorsed a number of ascetic and pietistic behaviors that are similar to those found in Sefer Ḥasidim and other texts of the German Pietists. A manuscript collection of rulings compiled by a student of Evreux, either Isaac b. Joseph or Pereẓ b. Elijah of Corbeil, includes an unusual ascetic eating practice of R. Moses that differs from those of several other European rabbinic scholars (and texts) at this time. This study proposes that Moses of Evreux was influenced by the thinking of an important earlier Tosafist in adopting this ascetic practice as a means of focusing more deeply and devotedly on Torah study. A careful reading of the section of the rulings in which this practice appears provides further evidence for this suggestion, and analogous eating behaviors in both northern and southern France in prior periods are identified and analyzed.